Territorial differentiation of the language situation in Sumy region as a factor of formation of regional identity - Hozhenko, Liudmyla; Siutkin, Sergii (Human Geography Journal, 2021)
The article considers the scientific and methodological principles of geographical study of the regional identity of the population, analyzes and assesses the current state of the language situation in the region and creates recommendations for the Ukrainianization of public life in the region. The main attention is paid to the study of the language situation in Sumy region by conducting questionnaires, analysis of markers of territorial identity and information flows. The relevance of this approach is explained by the role of language as one of the most important and stable ethnic characteristics. Gender and age of respondents, as well as place of residence (type of settlement) were taken into account. The key element of the article is the results of the study, which cover the spread of Ukrainian, Russian and surzhik (pidgin) in everyday life of the region, their level of awareness about Ukrainian language being a civic value, the desire to learn foreign languages as an indicator of geopolitical orientation. According to the results of the research, a series of maps and diagrams was created.An important manifestation of regional identity is toponymy, the names of local media, businesses and brands, catering establishments, hotels, sports teams and others. Ukrainian language as a mother tongue predominates in most administrative units of Sumy region. At the same time, the real bilingualism of the region's residents has formed the phenomenon of the most widespread so-called surzhik (pidgin) in Ukraine. Sumy region is not an integral historical and geographical region, perhaps that is why it does not have a high level of regional identity. The absence of obvious manifestations of separatism ensures a certain political stability in the region.The process of creating a Ukrainian political nation continues, so the recommendations for the Ukrainianization of public life are based on the analysis of existing practices, existing multimedia content in the actual "information war" and take into account the ethnogeographical specifics of the region, its border position and current socio-political situation.